1972
DOI: 10.1039/p19720002121
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pyrrolidine-2,4-diones(tetramic acids) and some derivatives

Abstract: Pyrrolidine-2.4-dione (tetramic acid) has been obtained by heating its 3-ethoxycarbonyl derivative with water or nitromethane. Prolonged heating with water yields 4-hydroxy-3,4'-bi-A3-pyrrolinyl-2,2'-dione, the anhydroderivative of the dione. Iand 5-Methylpyrrolidine-2,4-diones and their anhydro-derivatives have been obtained, similarly. Previously reported syntheses of these pyrrolidine-2,4-diones are shown to be in error; the products obtained appear to have been the corresponding anhydro-derivatives, or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

1972
1972
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…The parent compound 398 is a relatively weak acid, (pK a ¼6.4 in water), which exists in the keto from in the solid state, whereas in aqueous solution a minor contribution from the enol 399 may be discerned [626]. The enolization behavior of 3-acetyltetramic acids is more complex; studies involving for instance the 3-acetyl-5-isopropyl derivative revealed a considerable contribution from the exo-enol tautomer 400 [627].…”
Section: Transition Metal Catalyzed Coupling Reactionsmentioning
confidence: 97%
“…The parent compound 398 is a relatively weak acid, (pK a ¼6.4 in water), which exists in the keto from in the solid state, whereas in aqueous solution a minor contribution from the enol 399 may be discerned [626]. The enolization behavior of 3-acetyltetramic acids is more complex; studies involving for instance the 3-acetyl-5-isopropyl derivative revealed a considerable contribution from the exo-enol tautomer 400 [627].…”
Section: Transition Metal Catalyzed Coupling Reactionsmentioning
confidence: 97%
“…Chromatography, eluting with AcOEt, gave Ic as a light brown oil (2.7 g, 57% yield). IR ( Ethyl (4-Acetoxy-I,S-dihydro-2-oxo-2H-pyrrol-l-yl)acetate (8). Compound 4c (59.8 g, 300 mmol) was dissolved in AcOH (240 ml), at r.t., with stirring.…”
Section: Experimental Partmentioning
confidence: 99%
“…IR Spectra: Nicolet Model 20 SXB spectrometer; absorptions in crn-'. NMR Spectra: Varian Unity 400 (400 MHz for 'H-and 100.6 MHz for "C-NMR) spectrometer; chemical shifts (8) in ppm with reference to TMS; coupling constants ( J ) in Hz. MS: Hewlett-Packard HP 5989A.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Verbindungen dieses Typs sind bereits friiher hergestellt worden [8]. Sie konnen durch Kochen in Wasser verseift und decarboxyliert werden, wahrend bei alkalischer Verseifung und Decarboxylierung Selbstkondensationsprodukte, Anhydrodimere, entstehen [9]. Diese einfache Methode, auf 8 angewandt, ergab nur massige und schlecht reproduzierbare Ausbeuten an 9, ohne dass die Bildung von Kondensationsprodukten verhindert werden konnte.…”
Section: Nach Den Regeln Der Iupac-nomenklatur Ist 1 Als (5 S)-5-isopunclassified